Triage in Conservation - Matt W. Hayward (Frontiers Research Topics, 2018)
Ecosystems and their constituent species the world over face a barrage of ongoing, and often escalating, threats. Conservation efforts aim to reduce the impact of these threats to ensure that global biodiversity continues to provide essential ecosystem services. As is most often the case, these efforts to protect threatened species and their environments are constrained by limited resources. Conservation biologists have therefore had to increase the efficiency of their conservation practices to deliver the greatest benefit at the lowest cost. This requires decision making using the best available knowledge to prioritise actions. A concept that has received considerable attention in this area is that of conservation triage. This eBook brings together perspectives from researchers and conservation practitioners who share their views and results in an effort to extend the discussion on this topic. A number of the papers in this eBook tackle the philosophical elements of conservation triage, while others take a more directed practical approach providing examples from conservation practice globally.